Hubungan Pantangan Makanan terhadap Risiko Kekurangan Energi Kronik pada Ibu Hamil - Desta Stallaza Alifka (Yayasan Pendidikan Medika Indonesia, 2020)
Background: A person's nutrition needs to be designed from an early age, especially in the first 1000 days of life (HPK). Nutrition during pregnancy is one of the important factors affecting the development of the embryo and fetus as well as the health status of pregnant women. Chronic Energy Deficiency (CED) is one of the four main problems with the nutritional status of pregnant women in Indonesia. Content: Chronic energy deficiency (CED) is defined a condition where there is an imbalance between nutrients intake mainly energy and nutritional needs which lasts for years (chronic). Diagnose of CED is based on LILA <23.5 cm. The prevalence rate of CED risk in pregnant women has the largest percentage in the 15-19 years age group is around 33.5% and based the population of pregnant women who live in rural areas is 19.3%. The incidence of CED in pregnant women is influenced by direct factors and indirect factors. These factors are influenced by several circumstances, one of which is cultural perception. One of the problems that occur due to cultural / belief perceptions is the dietary consumption patterns of pregnant women such as the prohibition of certain types of food. Conclusion: Several research results indicate that there is a significant relationship between food taboo and the incidence of CED for pregnant women, especially if the type of food contains high nutrients which can affect the nutritional status of pregnant women.